गलकोटको राजनीतिक र सांस्कृतिक पृष्ठभूमि (The Political and Cultural Background of Galkot) - Thapa, Din Bahadur (International Research Journal of MMC, 2024)
नेपालभित्रको नेपाल भनेर चिनिने जिल्लाको नाम बागलुङ हो । बागलुङको मौलिक इतिहास र सांस्कृतिक पहिचान बोकेको स्थानीय तह भनेर गलकोट नगरपालिकालाई चिनिन्छ । यो पालिका कुनै समयमा ऐतिहासिक गलकोट राज्यका नामले चिनिन्थ्यो । गलकोटलाई चिनाउने अन्य विविध पहिचानहरू पनि छन् । तर यस लेखमा गलकोटको राजनीतिक र सांस्कृतिक पृष्ठाधारको मात्रै चर्चा गरिएको छ । गलकोट राज्यसँग राजपरम्परा र कोटथानको इतिहास जोडिएको छ । गलकोटमा मल्ल राजाहरुको १५ पुस्ताले राज्य गरेको इतिहास भेटिन्छ । कोटथानसँग माईथान, खड्गथान र हरेक जातजातिका परम्परित पूजाविधिको इतिहास जोडिएको छ । यो लेख गलकोटको राजनीतिक र सांस्कृतिक पृष्ठाधारको खोजी गर्ने उद्देश्यले तयार गरिएको हो । यसमा प्राथमिक स्रोतका सामग्रीहरु स्थलगत अवलोकन र अन्तर्वार्तामा आधारित छन् भने द्वितीयक स्रोतका सामग्रीहरू पुस्तकालयीय अध्ययनमा आधारित छन् । यस अध्ययनले गलकोटे राज परम्पराका केही अवशेषहरु मात्र बाँकी रहेको देखाउँछ भने राज परम्परासँगै स्थापना भएका कोटथान, माईथान, मस्टोथान, बराहथान, झाँक्रीथान र विभिन्न जातजातिको कुलपूजा पद्धतिमा पनि निरन्तरता, अनुकूलन र रुपान्तरणको गति तीव्र रहेको देखाउँछ । राजनीतिक र सांस्कृतिक रुपान्तरणसँगै यी कतिपय सम्पदाहरु लोपोन्मुख अवस्थामा रहेका देखिन्छन् । तसर्थ यी ऐतिहासिक र सांस्कृतिक सम्पदाहरूको संरक्षण गर्न आवश्यक छ । [Baglung, a district in Nepal, is often referred to as "Mini-Nepal." Galkot Municipality, functioning as a local government, embodies the district's fundamental historical and cultural identity. Historically, this municipality was known as the Galkot State, which holds significant political and cultural relevance. Although Galkot is associated with multiple identities, this article focuses specifically on its political and cultural background. The royal traditions and the historical significance of Kotthan are intricately linked to the Galkot State, which was ruled by 15 successive generations of Malla kings. The history of sites such as Maithan and Khadgathan, as well as the traditional rituals of various castes, are closely tied to Kotthan. This study explores the political and cultural heritage of Galkot, employing primary sources such as on-site observations and interviews, alongside secondary materials from library research. The findings indicate that only limited remnants of the Galkot royal traditions remain. However, the practices associated with kulpuja at Kotthan, Maithan, Mastothan, Barahthan, Jhankrithan, and other locations, as well as among different castes, have undergone significant processes of continuity, adaptation, and transformation. The study concludes that some of these historical and cultural heritages, which are at risk of degradation due to political and cultural changes, require urgent preservation by relevant stakeholders. This article aims to serve as an important reference for those interested in studying and safeguarding these historical and cultural legacies.]